Sensitization and its impact on Reproductive and sexual health issues of adolescents in clinics and schools - a comparative study. - De, Arun Kumar; Mitra, Souvik; Das, Kollol; Goswami, Sebanti; Chatterjee, Sukanta (Asian Journal of Medical Sciences, 2011)
Objective: Adolescent Reproductive and Sexual Health Issue is an important component of Youth Friendly Health Services. The objective of this study to compare the impact of sensitization on adolescent reproductive and sexual health issues of adolescent clients between clinic and school setting using the youth-friendly principles. Material & Methods: An urban–based prospective longitudinal study, conducted at adolescent health clinic and schools. The participants are adolescents in the age group of 14-18 years (both boys and girls). Intervention: Youth-friendly sensitization. Main outcome measures: Change in the knowledge on different ARSH issues among adolescent clients in both clinics and schools. Results: Statistically significant improvement (p values< 0.05) in knowledge on various aspects of ARSH issues among adolescent clients in both clinic and school setting. Conclusion: Youth-friendly sensitization makes positive change in the knowledge of adolescents on ARSH issues in both clinics and schools. Key Words: Adolescent; ARSH (adolescent reproductive and sexual health); Condom; Menstruation; Sensitization DOI: 10.3126/ajms.v2i1.3537 Asian Journal of Medical Sciences 2 (2011) 23-27